Consideration of a Phase Change Model Based on Apparent Phase Equilibrium. (November 2015) - Kashiwada, S; Iga, Y
Abstract: It has been known that cavity volume is underestimated and there is a discrepancy between predicted and measured breakdown characteristics for the numerical simulation of unsteady cavitation around a hydrofoil at high angle of attack. Therefore, in this study, in order to predict the cavity volume with high accuracy, the phenomena that gas phase increases even at a pressure higher than saturated vapour pressure which is known as aeration is modelled, and applied to phase change term. It was assumed that the precipitation of dissolved air is promoted by mechanical stimulation such as Reynolds stress in unsteady flow. The effectivity of the proposed model is discussed through the comparison among some kinds of components of the pressure variation.